Gendering postcolonial penality: The religious detention of women in Ireland - Black, Lynsey (Theoretical criminology, 2025)
The role of religion was pivotal in shaping how women were punished in postcolonial Ireland. The new state used the Catholic Church to establish a separate system of confinement, a shadow penal regime for women, which drew its inmates from within a newly recognized threat to the nation. Drawing on Mark Brown's work on the ways in which postcolonial states can replicate the repression of colonialism, the article suggests that under an increasingly morally authoritarian state, women perceived as sexually promiscuous found themselves in systems of religious control. This article explores the ‘how’ and the ‘why’ of this, examining the intersection of state and religious control through the cases of women convicted in the courts and sent to religious detention. I argue for the necessity of a gendered lens in postcolonial penality, and for consideration of the conditions of postcolonial nation formation in shaping punishment.